Characteristics and Indications of Kawasaki Disease Among Infants Under 6 Months - Tang, Yunjia; Li, Xuan; Cao, Lei; Chen, Ye; Yan, Wenhua; Xu, Qiuqin; Lv, Haitao (Frontiers in Pediatrics, 2020)
Objectives: To explore the characteristics of Kawasaki disease (KD) under six months and to investigate the possible indications of incomplete KD (iKD). Methods: The medical records of KD patients hospitalized in Children’s Hospital of Soochow University from January 2007 to December 2017 were retrospectively reviewed and analyzed. A total of 50 cases of urinary tract infection (UTI) and 50 cases of adenovirus (ADV) -infected patients under six months that were age and gender-matched with the main complaint of high fever were selected as controls. Results: A total of 1872 KD patients were enrolled. Among them, 194 (10.4%) were infantile patients under six months. There were 72 (37.1%) and 494 (29.4%) iKD in patients younger and older than six months, respectively (P < 0.05). Although patients under six months had a shorter fever duration before immunoglobulin (IVIG) treatment, a larger proportion of these patients had IVIG resistance and coronary artery lesions. They also tended to have higher platelet (PLT) counts and C-reactive protein (CRP) and lower hemoglobin (Hb), percentage of neutrophils (N%), albumin and serum sodium. When we compared iKD under six months with UTI and ADV-infected patients, significant differences were found in white blood cells (WBC), Hb, PLT, CRP, N% and serum albumin (P < 0.05). After adjusting the confounders, Hb < 105.5g/L, CRP > 22.7mg/L, N% > 47.4 and PLT > 496 × 109/L were indications of iKD when compared with ADV infection (area under the curve [AUC]: 0.872, 0.939, 0.707 and 0.684, respectively). N% > 51.8 and albumin < 39.0 g/L were indications of iKD when compared with UTI (AUC: 0.627 and 0.832, respectively). Conclusions: Infantile KD patients under six months had their own particularity. Laboratory variables could be good indications of iKD when compared with UTI and ADV infection.